Assessment of lower extremities ischemic disease by thallium 201 perfusion scintigraphy in patients with diabetic angiopathy - Čizmić Milica; Pucar Dragan; Zoranović Uroš (Vojnosanitetski Pregled)
Background/Aim. Tibial perfusion in diabetic microangiopathy is considered to be a diagnostic problem. A special place in quantifying muscle microcirculatory perfusion belongs to thallium 201 muscle perfusion scintigraphy (201Tl PS). Thallium, showing the characteristics of potassium (K+), enters a cell by means of active cell transportation and follows erythrocyte up to the tissue. The aim of this study was to determine if 201Tl PS of lower extremities (LE) is a good method for estimating muscle microcirculatory perfusion in diabetic microangiopathy. Methods. The study included 32 patients of an average age 66.1 ± 14.9 years with signs of LE ischemia befalling into III and IV stage of ischemic disease according to the Lariche-Fontain classification. Out of that number there were 27 of the patients with non-insulin-dependent diabetes mellitus (NIDDM), while 5 of the patients were with Burger's disease and Raynand's disorder. Lower extremities PS was performed after 3 min of tibial loading by the use of dorsoplantar foot flexion and intravenous 74 MBq 201Tl as a 10-minute dynamic study. A 10 minute static scintigraphy was carried out of the gluteal region, femurs, tibias and feet per a position and repeated after 3 h at rest in the same projections. The results were interpreted visually and by the semiquantitive method using a program for calculating the number of pulses per pixel in the corresponding region over 1-, 2- and 10-minute dynamic study, thus obtaining numerical data for estimating perfusion. Binding ratio in both legs was estimated visually as low (1), medium (2) and significant (3) difference in both legs. The results were compared with doppler hemodynamic indices (PI and RI). Results. Regardless the group, 201Tl binding intensity rising was significantly 2 min after application, as compared to 1 min, and the obtained level of binding was maintained even after 10 min. In the group Fontain III the majority of the patients showed a medium difference in binding 201Tl (2) in regard to the group Fontain IV with the patients having a low difference (1) between both legs and a significant difference between both legs (3). A statistically significant positive correlation was obtained between the values of RI index regarding distal region of a. tibialis posterior (p < 0.05, r = 0.43), as well as a. tibialis anterior (p = 0.05, r = 0.38). There was no correlation for the PI index. Low collateral net development based on the values for the indices PI and RI showed a less muscle perfusion on 201Tl in regard to medium and well developed collateral net with identical perfusion. Conclusion. The results of lower extremities perfusion scintigraphy are reliable indice of muscle microcilculatory perfusion. There is a statistically significant correlation between the doppler hemodynamic indices and 201Tl perfusion scintigraphy.